2018
DOI: 10.25215/0604.046
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Academic Self-Concept: A Founding Strategy in Learning Process

Abstract: Educators expect that the students perform optimally in order to support the achievement of learning objectives. However, they need to reflect the internal and external environments created to support the direction of the totality of students or vice versa. This study reports a qualitative investigation concerning to strategies that train the development of students’ academic self-concepts during the learning process. There were four sixth semester students of Physical Education, Health, and Recreation program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Academic self-concept concerns self-evaluation, self-perception of academic attitude and behaviour, and has two dimensions: change (flexibility to adapt) and stability (relatively stable psychologically) (Supervía et al, 2020). Although the potential effects of a coaching intervention on students' perception of inclusion have not been studied extensively, coaching among target groups in vocational education has been found to support a safe and inclusive learning environment (Christensen et al, 2021), and stimulate students' academic self-concept (Blegur et al, 2018).…”
Section: Wellbeing Perception Of Inclusion and Study-interestmentioning
confidence: 99%
“…Academic self-concept concerns self-evaluation, self-perception of academic attitude and behaviour, and has two dimensions: change (flexibility to adapt) and stability (relatively stable psychologically) (Supervía et al, 2020). Although the potential effects of a coaching intervention on students' perception of inclusion have not been studied extensively, coaching among target groups in vocational education has been found to support a safe and inclusive learning environment (Christensen et al, 2021), and stimulate students' academic self-concept (Blegur et al, 2018).…”
Section: Wellbeing Perception Of Inclusion and Study-interestmentioning
confidence: 99%
“…After conducting an exploratory study using participant observation methodologies, Blegur et al (2018) identified six tactics that can be used to teach students academic self-concepts during the learning process: 1) through the establishment of logical consequences that allow students to evaluate their own beliefs and efforts critically; 2) through the assignment of challenging responsibilities; 3) through the provision of dynamic expression media that empower students to think critically; 4) through the provision of solution-based feedback that motivates students to work hard; 5) through the practice of transparent evaluation of learning outcomes that allow students to feel good about their academic performance; and 6) through the integration of positive motivational thoughts that guarantee equal opportunity for all. Ajmal and Rafique (2018) found that students in the Rawalpindi region who were enrolled in Master of Education programs for one year or Bachelor of Education programs for 1.5 years had higher levels of academic self-concept as judged by the Liu and Wang (2005) academic self-concept scale.…”
Section: Review Studies On Metacognitionmentioning
confidence: 99%
“…It has been discovered that a child who feels himself to be confident performs well academically. A child who believes worthless is less confident and may not achieve their full potential [42]. Students with poor academic confidence have lower academic skills when they start college, are less interested and have more transition issues [43].…”
mentioning
confidence: 99%